MRI BRAIN APPEARANCES IN ANAPHYLAXIS: NOVEL OBSERVATIONS TO DIFFERENTIATE FROM GLOBAL HYPOXIC INSULT. (29th November 2012) - Warner, GT; Benjamin, J; MacKinnon, AD
Abstract : Global 'hypoxic brain injury' commonly presents typically after hypoperfusion, although true hypoxia may be absent. MRI is used to confirm clinical diagnosis is sought. However, a potentially different pattern of brain involvement may exist in the context of anaphylactic reactions. A previous well man (48) suddenly informed his co-worker of a wasp sting and rapidly lost consciousness. Paramedics were sought who arrived to find him in status epilepticus. He'd suffered a wasp sting 3 weeks earlier. Seizures came under control with standard anti-epileptic drugs and general anaesthesia on ITU. Acute brain CT (day 0) showed subtle reduced attenuation of the basal ganglia, progressing over 3 days to generalised cerebral sulcal effacement and symmetrical reduced attenuation of basal ganglia and much of the anterior circulation cortex. MRI (day 4) showed restricted diffusion, consistent with cytotoxic oedema, matching CT regions of low attenuation. Structures supplied by the posterior circulation, the limbic system, the insular and the medial perirolandic cortices were notably spared. Brain CT at 4 weeks showed atrophy in a similar distribution. Retrospectively although initial blood gases did not suggest severe hypoxia (base excess −2.6, pH 7.36) intubation was difficult probably reflecting laryngospasm. Ventilation indices did not suggest airflow limitation. Allergic rash was never observed. No specific measures were required to maintain blood pressure Raised blood tryptase released from mast cells supported diagnosis of significant anaphylaxis. Seizures were contained and ventilatory support withdrawn but he remains in a vegetative state. Although seizures may have contributed to or accentuated cortical MRI changes, this pattern of cytotoxic oedema has been previously described in anaphylactic shock (a Hoffmann J et al ). Discussion: Anaphylaxis resulted here from priming 3 weeks earlier. Chemical mediators of anaphylaxis may have caused differential vasoactive reaction in different cranial arteries compared to broad hypoperfusion of cardiac arrest or hypotension/shock, causing the specific distribution described. Novel conditions such as 'Post' Reversible Encephalopathy Syndrome (PRES) may reflect how posterior and anterior intracranial circulations react differently in specific clinical situations producing imaging changes in one geographical distribution compared to another. Appearances we describe are almost identical to those of Hoffmann et al and could represent new 'unrecognised' entity specific to anaphylactic reactions. Hypoxic brain injury sparing the posterior circulation. Jan Hoffmann, Katharina Erb, Randolf Klingebiel, and Eberhard Siebert. Neuroimages 2010 p1476.